Can Price Drive Repurchase Intention?The Mediating Role of Customer Satisfaction in Skintific TikTok E-Commerce in Malang - Rochma, Salwa Nisrina; Amelindha, Vania (Indonesian Journal of Islamic Economics and Business, 2025)
This study examines the impact of price on repurchase intention, with customer satisfaction serving as a mediating variable, among Skintific consumers on TikTok E-commerce in Malang City. The research employs a quantitative approach using a survey method, targeting 180 respondents who meet specific criteria, including prior purchases of Skintific products via TikTok. Data were collected using a Likert scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that price significantly influences both customer satisfaction and repurchase intention, highlighting the importance of competitive and fair pricing. Additionally, customer satisfaction mediates the relationship between price and repurchase intention, underscoring its role in fostering consumer loyalty. This study contributes to the digital marketing literature by demonstrating the interplay between pricing strategies and consumer behavior on social commerce platforms. The results imply that businesses can enhance repurchase intention by maintaining price fairness and improving customer satisfaction. Furthermore, the study underscores the relevance of TikTok E-commerce as a platform for engaging young consumers, particularly in urban areas like Malang. The novelty of this research lies in its focus on the TikTok E-commerce environment, which has become a prominent channel for digital marketing in Indonesia. Future research could explore additional factors, such as brand loyalty or promotional strategies, to further understand consumer behavior in this context